2006
DOI: 10.1074/jbc.m602203200
|View full text |Cite
|
Sign up to set email alerts
|

Recoverin Binds Exclusively to an Amphipathic Peptide at the N Terminus of Rhodopsin Kinase, Inhibiting Rhodopsin Phosphorylation without Affecting Catalytic Activity of the Kinase

Abstract: Recoverin is a calcium-dependent inhibitor of rhodopsin kinase. It prevents premature phosphorylation of rhodopsin until the opening of cGMP-gated ion channels causes a decrease in intracellular calcium levels, signaling completion of the light response. This calcium depletion causes release of recoverin from rhodopsin kinase, freeing the kinase to phosphorylate rhodopsin and to terminate the light response. Previous studies have shown that recoverin is able to bind to a region at the N terminus of rhodopsin k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
63
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 45 publications
3
63
0
Order By: Relevance
“…Recoverin Binding to RK25 and Rhodopsin-Previous studies have shown that recoverin interacts with the N-terminal 25 residues of RK (called RK25) (19,20). To determine the atomicresolution structural interaction of recoverin bound to RK25 by NMR, we first developed a recombinant RK25 construct expressed in E. coli that produces milligram amounts of isotopically labeled RK25 and without interference from glutathione S-transferase or other fusion partners (see "Experimental Procedures").…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recoverin Binding to RK25 and Rhodopsin-Previous studies have shown that recoverin interacts with the N-terminal 25 residues of RK (called RK25) (19,20). To determine the atomicresolution structural interaction of recoverin bound to RK25 by NMR, we first developed a recombinant RK25 construct expressed in E. coli that produces milligram amounts of isotopically labeled RK25 and without interference from glutathione S-transferase or other fusion partners (see "Experimental Procedures").…”
Section: Resultsmentioning
confidence: 99%
“…Ca 2ϩ -bound recoverin interacts with RK exclusively at residues 1-25 (19), and deletion of these residues also abolishes the kinase interaction with light-excited rhodopsin (20). According to surface plasmon resonance measurements, the N-terminal RK peptide binds to recoverin with micromolar affinity and only in the presence of Ca 2ϩ (19,20). Recoverin is structurally similar to other NCS proteins (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Under in vitro conditions, recoverin inhibits rhodopsin kinase (RK) 3 in a Ca 2ϩ -dependent manner resulting in extended activation of the visual pigment rhodopsin (3,4). Ca 2ϩ -bound recoverin binds the N-terminal helix of RK (5,6), an amphipathic helix also recognized by rhodopsin (7), and thus prevents phosphorylation of activated rhodopsin. When the Ca 2ϩ concentration is low, RK is released by recoverin and is then free to phosphorylate rhodopsin in a reaction that helps terminate the photoactivated state (8).…”
mentioning
confidence: 99%
“…Conversely, how GRK1 recognizes an activated receptor is far less understood. The N-terminal 30 amino acids of GRK1 appear to be critical for receptor recognition, because the in vitro binding of Ca 2ϩ -recoverin to this region (17,18) or the binding of an antibody directed against GRK1 residues 17-34 (19) inhibits receptor phosphorylation yet has no effect on GRK1-mediated phosphorylation of peptide substrates.…”
mentioning
confidence: 99%